Development of the lentiviral vector with GC-rich segment of the promoter region of fusion oncogene RUNX1-RUNX1T1 - Saurytskaya, Hanna A.; Ilyushonak, Ilya M.; Grinev, Vasily V. (Experimental Biology and Biotechnology, 2018)
As is known, a PCR-cloning of GC-rich regions and development the vectors with such sequences can be non trivial. In this work we performed an optimization of PCR-amplification protocol for segment of internal promoter region of fusion oncogene RUNX1-RUNX1T1 and developed of multipurpose lentiviral vector with insertion of this sequence. We generalize our experience of dealing with GC-rich sequences in some methodological recommendations.